Disparities of population exposed to flood hazards in the United States - Qiang, Yi (Journal of environmental management, 2019)
This study integrates publicly available datasets to provide a county-based assessment of socio-economic disparities of population exposure to flood hazards in the United States. Statistical analyses were applied to reveal the national trends and local deviations from the trends. Results show that approximately 21.8 million (6.87% of) U.S. population are exposed to 100-year-flood in 2015, and most of the exposure is near water bodies (e.g. ocean and rivers). Additionally, communities near water bodies are more responsive to potential flood hazards by avoiding residence in flood zones than inland communities. At the national scale, economically disadvantaged population are more likely to reside in flood zones than outside. At the local scale, economically disadvantaged population tend to reside in flood zones in inland areas, while coastal flood zones are more occupied by wealthier and elderly people. These findings point to an alarming situation of inland communities where people are generally less responsive to flood hazards and people in flood zones are in a lower economic condition. Using “hot spot” analysis, local clusters of disadvantaged population groups with high flood exposure were identified. Overall, this study provides important baseline information for policymaking at different levels of administration and pinpoints local areas where diversified and ad hoc strategies are needed to mitigate flood risk in communities with diverse socio-economic conditions. This study provides empirical evidence of socio-economic disparities and environmental injustice associated with flood exposure in the U.S. and offers valuable insights to the underlying factors. •21.8 million (6.87%) U.S. population are exposed to 100-year-flood.•Coastal and riverine communities are more responsive to flood hazards.•Nationally, economically disadvantaged population tend to reside in flood zones.•Economically disadvantaged people tend to reside in flood zones in inland areas.•Old and wealthy people are more crowded in coastal flood zones.